O-002 Predictors of unfavorable outcomes and mortality despite successful recanalization: an analysis of ARISE II data. (22nd July 2019) - Siddiqui, A; Waqas, M; Andersson, T; Saver, J; Mattle, H; Bozorgchami, H; Chapot, R; Narata, A; Yoo, A; Ribo, M; Zaidat, O
Abstract : Background: A significantly large number of patients with emergent large vessel occlusion (ELVO) fail to achieve favorable outcomes despite successful recanalization. Why some patients do not achieve functional independence despite successful revascularization is an important question. There is a paucity of prospective data on the predictors of unfavorable outcomes despite successful recanalization during mechanical thrombectomy for ELVO. Objective: This study was performed to determine the predictors of unfavorable outcomes in patients receiving successful recanalization (modified thrombolysis in cerebral infarct, mTICI grade ≥2b) in a prospective multicenter cohort of patients with ELVO. Methods: This was a secondary analysis of data collected from ARISE II study (Analysis of Revascularization in Ischemic Stroke With EmboTrap). ARISE II was a prospective, multicenter single arm study on the efficacy of EmboTrap Revascularization Device. Patients who achieved mTICI score of 2b or greater within 3 passes were included in this study. Patients with incomplete follow up were excluded from the study. A univariate and multivariate logistic regression was performed to determine the independent predictors of unfavorable outcomes at 90 days (defined as mRS 3–6). The variables tested as predictors included age, gender, collateral grade, ASPECTS, mode of transfer, National health institute stroke scale (NIHSS) score, use of intravenous tissue plasminogen activator, number of passes, clot location, final mTICI and symptomatic intracranial hemorrhage (sICH). Odds ratio (OR) with 95% confidence interval (CI) were reported. Results: One hundred seventy six patients were included in this secondary analysis of ARISE II data. Unfavorable outcomes (mRS=3–6) at 3 months were seen in 52 (29.6%) patients. Females constituted 54.88% of total population. Mean age was 67.15 years. Mean NIHSS score was 15.85±4.71. M1 was the most common site of occlusion with 54.55% followed by M2 (25.0%) and ICA (15.91%). Delay from stroke onset to the deployment of stent retriever was 3.97±1.44 hours. Ninety (51.14%) patients required a single pass. On univariate logistic regression analysis age, ASPECTS, collateral grade, time from stroke onset to the deployment of stent retriever, duration of procedure, NIHSS score, and sICH were found to be significant predictors of unfavorable outcomes. On multivariate analysis collateral grade (OR, 0.24, 95% CI 0.06–0.94, p value 0.04), NIHSS score (OR 1.28, 95% CI 1.15–1.43, p value <0.001), and number of passes (OR, 2.08, 95% CI 1.40–3.10, p value 0.0003) were found to be independent predictors of unfavorable outcomes in patients with successful recanalization. Conclusion: Collateral grade, NIHSS score at presentation, and number of passes are independent predictors of unfavorable outcomes at 90 days. Disclosures: A. Siddiqui: 1; C; Co-investigator NIH/NINDS 1R01NS091075. 2; C; Canon Medical System US, Boston Scientific, Amnis Therapeutics, Cerebrotech Medical Systems, Silk Road, Corindus Inc., Blockade Medical, Guidepoint Global Consulting, Imperative Care, Integra LifeSciences Corp, Medtronic, MicroVention, Q'Apel Medical Inc, Rapid Medical, Rebound Therapeutics Corp., Serenity Medical Inc, Silk Road Medical, StimMed, Stryker, Three Rivers Medical, VasSol, W.L. Gore & Associates. M. Waqas: None. T. Andersson: 2; C; Neuravi, Ablynx, Amnis Therapeutics, Medtronic, Rapid Medical, Stryker. J. Saver: 1; C; Medtronic-Abbott, Neuravi. H. Mattle: None. H. Bozorgchami: None. R. Chapot: None. A. Narata: None. A. Yoo: 1; C; Penumbra, Neuravi, Cerenovus. M. Ribo: None. O. Zaidat: 2; C; Stryker, Medtronic, Neuravi, Penumbra.